Eksistensi Kelayakan dan Hubungan antara Pengusahaan Pertambangan dengan Politik pada Masa Pemilu (SETARA : Jurnal Ilmu Hukum, 2024)
This study examines the feasibility and relationship between mining business and politics during elections, as well as the symbiotic relationship between the mining sector and politics in the Indonesian electoral context. The research method is empirical juridical, beginning with secondary data research and followed by primary data analysis in the field. The research combines library and field research. The study indicates that the economic power of the mining sector may be used by political actors to secure business interests. This practice creates a mutually beneficial cycle in which mining entrepreneurs finance political campaigns while elected politicians provide policies favorable to the mining sector. Article 33 of the 1945 Constitution risks becoming an illusion for the people and the state when oligarchic power not only strips economic resources from the state but also captures political authority.